2018
DOI: 10.2298/aoo180201004w
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence and social support among Indonesian gynecological cancer survivors

Abstract: Background: Fear of cancer recurrence is a long-term psychological problem of the cancer survivors regardless of the type of cancer. A growing number of studies had addressed fear of cancer recurrence, yet they are largely focused on the breast cancer survivors of the western world countries. This study investigates the fear of cancer recurrence and its relations to social support in Indonesian gynecological cancer survivors. Methods: Gynecological cancer survivors (n = 153) in Samarinda, East Kalimantan, Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Accordingly, Myers et al [ 24 ] found that among women diagnosed with gynecological cancer, not sharing concerns and negative responses from family and friends were related to increased FCR and, in turn, increased cancer-specific stress. Likewise, Wijayanti et al [ 25 ] found that among gynecological cancer survivors, those with higher social support were more likely to experience lower levels of FCR. Moreover, several quantitative studies noted that spouses of cancer survivors are typically found to have greater levels of FCR than the patients themselves [ 6 ], and patient and spouse FCR scores have been found to correlate within-dyad [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Myers et al [ 24 ] found that among women diagnosed with gynecological cancer, not sharing concerns and negative responses from family and friends were related to increased FCR and, in turn, increased cancer-specific stress. Likewise, Wijayanti et al [ 25 ] found that among gynecological cancer survivors, those with higher social support were more likely to experience lower levels of FCR. Moreover, several quantitative studies noted that spouses of cancer survivors are typically found to have greater levels of FCR than the patients themselves [ 6 ], and patient and spouse FCR scores have been found to correlate within-dyad [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…36,37 See Table 1 for further details. FCRI-total scores (score range 0-168) were reported in 25 studies, with mean scores ranging from 39.8 in a sample of prostate cancer survivors 11 to 113.5 in a sample of gynecological cancer survivors. 39 The reported standard deviations ranged from 18.6 to 39.5 with an average of 28.2, samples sizes varied from 27 to 1984 and the mean time since diagnosis ranged from 4.1 months to 16.5 years. As shown in Table 1, the overall combined, weighted mean FCRI-Total score across all cancer types was 65.2 (95% CI: 58.0-72.3).…”
Section: Fcr Severity and Prevalence According To The Fcrimentioning
confidence: 99%
“…For example, Japanese women with low self-esteem, undergoing treatment for cervical cancer, were more likely to suffer from psychological distress than those with high self-esteem [ 57 ]. Chinese women with recurrent ovarian cancer had high rates of anxiety and depression prior to chemotherapy [ 49 ], and fear of cancer recurrence impacted women’s mental health [ 35 , 37 , 47 , 51 , 65 , 66 , 73 ]. In Indonesia, older women with gynaecological cancer of any type were more likely than younger women to fear recurrence [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chinese women with recurrent ovarian cancer had high rates of anxiety and depression prior to chemotherapy [ 49 ], and fear of cancer recurrence impacted women’s mental health [ 35 , 37 , 47 , 51 , 65 , 66 , 73 ]. In Indonesia, older women with gynaecological cancer of any type were more likely than younger women to fear recurrence [ 66 ]. Lower income and family history of cancer were also associated with fear of recurrence and treatment failure [ 66 ].…”
Section: Resultsmentioning
confidence: 99%